PERLINDUNGAN HUKUM TERHADAP HAK PATEN DI INDONESIA - Gumanti, Retna (Al-Mizan, 2015)
An intellectual work is very important to be given an award for the effort and the success of an attempt to create it. This study is the role of government to guarantee legal protection for intellectual property rights. This paper discusses the legal protection of patent rights in Indonesia. It is used the legal approach with methods of critical analysis of law. The results showed that Law No. 14 of 2011 on Patents has provided unequivocal protection for the owner of the patent-infringing patents against infringement.